Breathing Exercise Relaxation Increase Phsycological Response Preschool Children - Yuni Sufyanti Arief; Nuzul Qur’aniati; Fransisca Kristiningsih (Jurnal Ners, 2008)
Introduction: Being hospitalize will be made the children become stress. Hospitalization response of the child particularly is afraid sense regard to painfull procedure and increase to attack the invasive procedure. The aimed of this study was to describe the influence of breathing exercise relaxation technique regarded to phsycological receiving responses in the preeliminary school chidren while they were receiving invasive procedure. Method: A quasy experimental purposive sampling design was used in this study. There were 20 respondents who met to the inclusion criteria. The independent variable was the breathing exercise relaxation technique and the dependent variable was phsycological receiving responses. Data for phsylogical response were collected by using observation form then analyzed by using Wilcoxon Signed Rank Test and Mann Whitney U Test with significance level α≤0.05. Result :  The result showed that breathing exercise relaxation technique had significance influence to phsycological response (p=0.000). Discussion: It,s can be concluded that breathing exercise relaxation technique has an effect to increase pshycological response in preeliminary school children who received invasive procedure.